Current Incidence and Risk Factors of Fecal Incontinence After Acute Stroke Affecting Functionally Independent People - Lucente, Giuseppe; Corral, Javier; Rodríguez-Esparragoza, Luis; Castañer, Sara; Ortiz, Hector; Piqueras, Anna; Broto, Joaquim; Hernández-Pérez, María; Domenech, Sira; Martinez-Piñeiro, Alicia; Serra, Jordi; Almendrote, Miriam; et al. (Frontiers in Neurology, 2021)
Background: Limited and previous retrospective series show a high prevalence of fecal incontinence(FI) in stroke patients. We aimed to analyze in a prospective series the current incidence of FI in acute stroke in functionally independent patients and its evolution over time and the patient characteristics associated with the appearance of FI in acute stroke. Methods: We included consecutive patients with acute stroke admitted in our stroke unit who fulfilled the following inclusion criteria: a first episode of stroke, aged>18 years, with no previous functional dependency (modified Rankin Scale (mRS) ≤2) and without previous known FI. FI was assessed by a multidisciplinary trained team using dedicated questionnaires at 72±24hours (acute phase) and at 90±15 days (chronic phase). Demographic, medical history, clinical and stroke features, mortality and mRS at 7 days were collected Results: 359 (48.3%) of 749 patients (mean age 65.9±10, 64% male, 84.1% ischemic) fulfilled inclusion criteria and were prospectively included during a 20-month period. FI was identified in 23 patients (6.4%) at 72 hours±24 hours and in 7 (1.9%) at 90 days±15 days after stroke onset. FI was more frequent in hemorrhagic strokes (18%vs5%, p 0.007) and in more severe strokes (median National Institute of Health Stroke Scale (NIHSS) 18 [14-22] vs. 5[3-13] p<0.0001). No differences were found regarding age, sex, vascular risk factors or other comorbidities or affected hemisphere. Patients with NIHSS≥ 12(AUC 0.81, 95% CI 0.71 to 0.89) had a 17-fold increase for the risk of FI (OR 16.9 IC 95% 4.7–60.1) adjusted for covariates. Conclusions: At present, the incidence of FI in acute stroke patients without previous functional dependency is lower than expected, with an association with a more severe and hemorrhagic stroke. Due to its impact on the quality of life it is necessary to deepen the knowledge of the underlying mechanisms to address therapeutic strategies